EVALUASI PENGELOLAAN SAMPAH RUMAH SAKIT PUSAT ANGKATAN DARAT GATOT SOEBROTO - Paramita, Nadia (Universitas Diponegoro, 2007)
Activity in a hospital producing organic and inorganic solid waste.the characteristics of the solid waste are devided into domestic and medical which have to be destroyed immidiatly, so they wont coused any environmental problems. One way to prevent the danger coused by those waste is using the right hospital waste management from the source until the destruction parts. In waste management, it is important separate between medical and non medical waste from the source than continue with the right storage, and transportation steps. To destroy medical waste, controlled air incinerator with multychamber is recommended incinerator technology. With two steps of burning processes will make complete combustion. Experiment of medical waste incinerator with abaout 5 m3 capacitiesshows the batch combustion system at 800-1600 ºC temperature. Using that incinerator, the volume of this medical solid waste can be reduceduntil ± 67 % and mass reduction until 70-80 %.